Increased Behavior of Students' Attitudes to Cultural Values Using the Inquiry Learning Model Assisted by Ethnoconstructivism - Syahrial Syahrial; Asrial Asrial; Dwi Agus Kurniawan; Putut Nugroho; Retno Septiasari; Reza Aditya Pratama; Rahmat Perdana (Universitas Negeri Makassar, 2019)
Purpose: Student attitudes toward cultural values are needed in 21st century learning. Research with a focus on improving student attitudes towards cultural values using inquiry-based approaches. Therefore, this quasi-experimental quantitative research aims to improve student attitudes to the cultural values of elementary school teacher education students with an inquiry model assisted by the ethnoconstructivism module. Methodology: uses a quantitative design of quasi-experimental pretest-posttest non-equivalent control group design. Where the number of all samples from this study were 86 elementary school teacher education students taken by purposive sampling technique. The experimental group (n = 43) was taught with the inquiry learning model assisted by the ethnoconstructivism module, while the control group (n = 43) was taught using traditional teaching modul. The data were then analyzed using the SPSS 21 application to find descriptive statistics and inferential static. Findings: There was a significant difference in the attitude of students between the control class and the experimental class. It was found that using ethnoconstructivism inquiry models obtained differences with t-test values 18,473 on student attitudes. It can be underlined that the inquiry model with ethnoconstructivism has a significant influence on student attitudes towards cultural values compared to conventional groups